1996
DOI: 10.1017/s0022029900031563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and temperature on the water-holding capacity of casein curds and whey protein gels

Abstract: SummaryThe water-holding capacities of mineral acid casein (MAC) curd, rennet casein curd and whey protein concentrate (WPC) gel were determined as a function of pH and temperature by drainage of liquid on a stationary, horizontal screen. As precipitation pH was varied over the range 4·3–5·55, the water-holding capacity of MAC curd ranged from 2·4 to 5·2 g water/g dry casein with minimum water-holding capacity at precipitation pH 5·3. Samples of dried MAC curd over the same range of precipitation pH did not va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…This was because the protein contents of the UFSD and UFVESD were comparable (Ji, 2000) and protein structure was perhaps not altered significantly by the VE process. Teo et al (1996) reported a decrease in WHC of WPC gels with an increase in temperature in the range of 5-90˚C. Kneifel et al (1990) observed a steady increase in WHC of caseinates with an increase in temperature of preheating skim milk from 60 to 120˚C with a 10˚C increment.…”
Section: Resultsmentioning
confidence: 96%
“…This was because the protein contents of the UFSD and UFVESD were comparable (Ji, 2000) and protein structure was perhaps not altered significantly by the VE process. Teo et al (1996) reported a decrease in WHC of WPC gels with an increase in temperature in the range of 5-90˚C. Kneifel et al (1990) observed a steady increase in WHC of caseinates with an increase in temperature of preheating skim milk from 60 to 120˚C with a 10˚C increment.…”
Section: Resultsmentioning
confidence: 96%
“…the same range as those found by Jablonka and Munro 1986 Ž . and Teo et al 1996a . At an aging time of 10 min, the solids content decreased linearly from 19.9% at an acidification time of 1.5 min to 17.6% at 16 min.…”
Section: Solids Content Of the Precipitatementioning
confidence: 98%
“…It was suggested that the calcium binding was a Ž . cause for the higher particle size Teo et al 1996a . The results on the influence of temperature that were found in this Ž .…”
Section: Influence Of the Temperature And The Amount Of Acid Addedmentioning
confidence: 98%
“…The manufacturing processes for casein and caseinates have been reviewed recently by Mulvihill (1989). Efficient operation of the solid-liquid separation devices at the dewheying and dewatering stages and between each stage of the washing process requires some knowledge of the water-holding capacity of the casein curd as elaborated by Teo et al (1996). Ionic strength, pH and temperature are the main physicochemical variables known to affect curd water-holding capacity.…”
mentioning
confidence: 99%
“…The physicochemical effects of washing on the curd water-holding capacity were not considered. Teo et al (1996) have shown that washing caused a dramatic reduction in the water-holding capacity of both mineral acid casein (MAC) and rennet casein (RC) curds. For MAC curd the water-holding capacity was calculated to be 8-18 g water/g dry casein after acidulation and 4-66 g water/g dry casein after the final wash. O'Meara & Munro (1982) reported that the shrinkage of MAC curd on entering the first wash was very rapid with the final curd volume reached within ~ 1 min.…”
mentioning
confidence: 99%